Home-based Functional Electrical Stimulation for long-term denervated human muscle: History, basics, results and perspectives of the Vienna Rehabilitation Strategy - Helmut Kern; Ugo Carraro (PAGEPress Publications, 2014)
We will here discuss the following points related to Home-based Functional Electrical Stimulation (h-b FES) as treatment for patients with permanently denervated muscles in their legs: 1. Upper (UMN) and lower motor neuron (LMN) damage to the lower spinal cord; 2. Muscle atrophy/hypertrophy versus processes of degeneration, regeneration, and recovery; 3. Recovery of twitch- and tetanic-contractility by h-b FES; 4. Clinical effects of h-b FES using the protocol of the "Vienna School"; 5. Limitations and perspectives. Arguments in favor of using the Vienna protocol include: 1. Increased muscle size in both legs; 2. Improved tetanic force production after 3-5 months of percutaneous stimulation using long stimulus pulses (> 100 msec) of high amplitude (> 80 mAmp), tolerated only in patients with no pain sensibility; 3. Histological and electron microscopic evidence that two years of h-b FES return muscle fibers to a state typical of two weeks denervated muscles with respect to atrophy, disrupted myofibrillar structure, and disorganized Excitation-Contraction Coupling (E-CC) structures; 4. The excitability never recovers to that typical of normal or reinnervated muscles where pulses less than 1 msec in duration and 25 mAmp in intensity excite axons and thereby muscle fibres. It is important to motivate these patients for chronic stimulation throughout life, preferably standing up against the load of the body weight rather than sitting. Only younger and low weight patients can expect to be able to stand-up and do some steps more or less independently. Some patients like to maintain the h-b FES training for decades. Limitations of the procedure are obvious, in part related to the use of multiple, large surface electrodes and the amount of time patients are willing to use for such muscle training.